WAYS TO INCREASE THE EFFECTIVENESS OF CLEANING IMPURITIES IN COTTON - A. Mirzaakbarov (European Science Publishing, 2024)
Effective research has been carried out for several years on ginning cotton and obtaining high-quality fiber by purifying the bleak added to cotton. This article analyzes the technologies proposed by scientists from foreign countries and scientists from our republic.
Keywords: cotton, fiber, uluk, seed, cleaning, impurities.